The Enhancement of Pool Boiling Heat Transfer by Passive Technique using Rotating Blades Applied on the Nucleation Sites - A. Suriyawong; S. Saisorn; A. Kawahara; S. Wongwises (My University, 2019)
This paper was aimed to investigate the nucleate boiling phenomena with the presence of the rotating blades above the heat transfer surface. The boiling process at 1 atm was carried out by allowing heat transferred from a copper surface to distilled water. The 4-blade rotor made from copper was vertically installed at different distances above the heat transfer surface (LSB). The flow visualization during phase-change phenomena under heat flux values of 160-610 kW/m2 was feasible by high-speed camera. The results showed that pool boiling at the heat flux of 160 kW/m2 corresponded to isolated bubble regime, and at the value of 610 kW/m2, the column regime was observed. In addition to the two-phase flow pattern, the heat transfer coefficient data was reported in this work. The heat transfer results were found to depend on the distance at which the rotor was installed.
Keywords: Heat Transfer and Boiling Studies